A redox-active radical as an effective nanoelectronic component: stability and electrochemical tunnelling spectroscopy in ionic liquids. Issue 40 (3rd October 2016) - Rudnev, Alexander V.; Franco, Carlos; Crivillers, Núria; Seber, Gonca; Droghetti, Andrea; Rungger, Ivan; Pobelov, Ilya V.; Veciana, Jaume; Mas-Torrent, Marta; Rovira, Concepció
Abstract : PTM radical exhibits effective redox-mediated enhancement of tunnelling current, demonstrating its applicability as an active nanoelectronic component. Abstract : A redox-active persistent perchlorotriphenylmethyl (PTM) radical chemically linked to gold exhibits stable electrochemical activity in ionic liquids. Electrochemical tunnelling spectroscopy in this medium demonstrates that the PTM radical shows a highly effective redox-mediated current enhancement, demonstrating its applicability as an active nanometer-scale electronic component.